Analisis Bibliometrik Pengaruh Teknik EFT Terhadap Kecemasan Pada Masa Depan - Annora Malva Lena; Ulil Azmil; Tri Wahyu Arifuddin (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
This study aims to explore how research on the Emotional Freedom Technique (EFT) and its impact on future anxiety has developed, using a bibliometric approach. EFT is a psychological method that combines exposure therapy, cognitive techniques, and stimulation of meridian points in the body. In recent years, this technique has become more popular in helping people deal with anxiety, including worries about the future, which are often caused by life uncertainties, career challenges, and social changes. This study shows trends in publications, author collaborations, main keywords, and relevant journals to provide a clearer picture of research on this topic.